Theoretical framework used in parental involvement research: a scoping review - Solichah, Novia; Fardana, Nur Ainy; Samian, Samian (Institute of Advanced Engineering and Science, 2025)
Theoretical perspectives are important in framing a research model of parental involvement. Despite numerous studies examining parental involvement, their findings continue to exhibit inconsistency when viewed through a theoretical lens. A literature review conducted in 2017 examined the theoretical frameworks employed in parental involvement studies conducted between 2007 to 2011. The primary objective of this study is to analyze and offer novel insights into the theoretical perspectives that underpin parental involvement research, adhering to PRISMA guidelines. We conducted an extensive study of literature published between 2012 to 2023 that met the following inclusion criteria: research papers, reports on parental involvement, and reports on theoretical framework. Our study encompassed a systematic search of electronic databases, including Scopus, EBSCO Sciences, Emerald, and Science Direct from July to September 2023 to identify relevant articles. A total of 366 articles were obtained, and 44 articles met the criteria. Four theories frequently utilized in parental involvement research emerged from this study, namely Bronfenbrenner’s Bioecological Theory; Bourdieu, Coleman, and Lareau’s social capital; Social Identity Theory; and Ajzen’s Theory of Planned Behavior. The findings of this research serve as a foundational resource for future research on parental involvement across diverse contextual settings.